2016
DOI: 10.1371/journal.pone.0160854
|View full text |Cite
|
Sign up to set email alerts
|

Intrastriatal Grafting of Chromospheres: Survival and Functional Effects in the 6-OHDA Rat Model of Parkinson's Disease

Abstract: Cell replacement therapy in Parkinson’s disease (PD) aims at re-establishing dopamine neurotransmission in the striatum by grafting dopamine-releasing cells. Chromaffin cell (CC) grafts produce some transitory improvements of functional motor deficits in PD animal models, and have the advantage of allowing autologous transplantation. However, CC grafts have exhibited low survival, poor functional effects and dopamine release compared to other cell types. Recently, chromaffin progenitor-like cells were isolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…However, DNLA increased the time stay on rotarod test and the number of DA neurons. These findings were in accordance with previous research reported that 6-OHDA (8-12 μg/rat) induces movement disorder as main symptom of PD by decreasing the number of DA neurons in SNpc [26,27].…”
Section: Discussionsupporting
confidence: 93%
“…However, DNLA increased the time stay on rotarod test and the number of DA neurons. These findings were in accordance with previous research reported that 6-OHDA (8-12 μg/rat) induces movement disorder as main symptom of PD by decreasing the number of DA neurons in SNpc [26,27].…”
Section: Discussionsupporting
confidence: 93%
“…Due to their favorable properties, chromospheres could represent a new and promising source for cell replacement therapy in Parkinson´s disease as a significantly higher population of chromospherederived cells has been shown to acquire a dopaminergic phenotype compared to chromaffin cells (Boronat-Garcia et al, 2016;Vukicevic et al, 2012).…”
Section: ))mentioning
confidence: 99%
“…To measure dopaminergic imbalance, animals were injected intraperitoneally with 4 mg/kg amphetamine (Sigma-Aldrich). The number of turns was recorded for 90 min using a custom-made computerized image and motion recognition system [24]. Animals were evaluated two weeks after injury, and only those with more than 400 ipsilateral turns were selected for transplantation procedures.…”
Section: Rotational Behaviormentioning
confidence: 99%
“…Immuno uorescence assays were performed as previously described [24]. Brain slices were rinsed three times in PBS/0.3% Triton X-100 (Sigma-Aldrich), treated with antigen retriever in citrate buffer (BioSB) at 65°C for 30 min, and washed three times with PBS.…”
Section: Histology and Immuno Uorescence Stainingmentioning
confidence: 99%